HYPOGLYCEMIC AND ANTIHYPERLIPIDEMIC EFFECTS OF ADIANTUM CAUDATUM IN ALLOXAN INDUCED DIABETES IN RATS - Saha, Dipankar; Kumar Ghosh, Surajit; Das, Trishna; Mishra, Shanti Bhushan (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To investigate the hypoglycemic and antihyperlipidemic effect of a successive ethanolic extract of Adiantum caudatum (EEAC) whole plant in alloxan induced diabetic rats. Methods: Diabetes was induced in Wistar albino rats by the administration of alloxan (140 mg/kg b. w., i.p.). EEAC (200 mg/kg b. w., p.o.) was administered to diabetic rats for 21 days in alloxan induced diabetic rats. The effect of EEAC on blood glucose and body weight was studied in alloxan induced diabetic rats. All these effects were compared with glibenclamide (10 mg/kg b. w., p.o.) as a reference antidiabetic drug. Results: The administration of EEAC (200 mg/kg b. w., p.o.) resulted in a significant decrease in blood glucose level and a significant increase in body weight in alloxan induced diabetic rats. Furthermore, EEAC showed antihyperlipidemic activity as evidenced by a significant decrease in serum total cholesterol and triglyceride levels in alloxan induced diabetic rats. Conclusion: The results suggest that the EEAC possess a promising hypoglycemic effect in alloxan induced diabetic rats. Keywords: Hypoglycemic, Antihyperlipidemic, Adiantum caudatum, Alloxan, Diabetes.